2014
DOI: 10.1002/chir.22313
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stable Alleno‐Acetylenic Cyclophanes Bearing Chiral Axes

Abstract: The design and synthesis of chiral cyclophanes containing signaling functional groups as an integral part of the macrocyclic framework offer promising possibilities for chiral sensing, molecular recognition, and chiral supramolecular architectures. Our research group has been involved in the construction and study of chiroptical properties of several allenic meta- and para-cyclophanes bearing anthracene and pyridine rings as spacers. A revision of our results is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Thus, following the methodology developed in our group, , 3 was prepared in 62% overall yield from DEA vía 4 , which underwent an alkyne homocoupling process under Breslow conditions at room temperature once the protecting groups were removed (Scheme ). ( P , P )- 3 showed a high chiroptical response with a g -factor value of 0.007 with no loss of CD intensity under ambient conditions (Figure a).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Thus, following the methodology developed in our group, , 3 was prepared in 62% overall yield from DEA vía 4 , which underwent an alkyne homocoupling process under Breslow conditions at room temperature once the protecting groups were removed (Scheme ). ( P , P )- 3 showed a high chiroptical response with a g -factor value of 0.007 with no loss of CD intensity under ambient conditions (Figure a).…”
mentioning
confidence: 75%
“…Chiral macrocyclic systems have shown broad applicability as molecular receptors. , The high sensitivity of chiroptical responses to conformational changes and intermolecular interactions would furnish chiral shape-persistent macrocycles ,, with outstanding sensing capabilities. In this regard, the use of systems with narrow conformational space is desired in order to maximize chiroptical response intensities. , Therefore, we considered allenophanes as good candidates to build highly responsive chiral macrocycles since allenes offer both requirements: chirality and conformational rigidity. During the last years, diethynylallenes (DEAs), along with aromatic connectors, have already been used to create structures with different shapes, sizes, and functionalities. …”
mentioning
confidence: 99%
“…Enantioselective interaction of two (M) helical cavities (black helical spheres) with two enantiomers of helicene, favoring the complexation of the one that maximizes the interactions There are several motifs apart from stereogenic centers that impart chirality to a molecule, such as chiral axes, 8 including allenes, 9,10 spirocyclic systems, 11 alkylidenecycloalkanes; chiral planes, such as cyclophanes or organometallic sandwich compounds; helical moieties, such as helicenes 12 and cyclotriveratrylenes; 13 and biaryls as long as they bear different substituents at both ends ( Figure 2). 14,15 Shape-persistent systems are currently the target of intense scientific research because they hold a well-defined cavity that bestows them with potential applications in catalysis or sensing, among others, as they provide discrimination in terms of size, shape, and function complementarity in a 3D array.…”
Section: Figurementioning
confidence: 99%
“…Our research group has reported several publications involving the construction and study of the chiroptical properties of several allenic metaand para-cyclophanes bearing pyridine and bipyridine rings as spacers. 9,78 The presence of pyridine rings allowed the formation of an organometallic tetracarbonyl rhenium compound of the type [PyRe(CO) 4 Br] in which the lowest-energy absorption was assigned to a metal-ligand-to-ligand charge transfer transition. 79 This kind of Re complex is uncommon in the literature.…”
Section: Short Review Syn Thesis 22 Heteroatom-containing Macrocyclesmentioning
confidence: 99%
See 1 more Smart Citation